2010
DOI: 10.4067/s0370-41062010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Prevención del Dolor en Recién Nacidos de Término: Estudio Aleatorizado Sobre Tres Métodos

Abstract: Pain prevention in term neonates: randomised trial for three methods Introduction: Every newborn infant is screened for hypothyroidism and phenilketonuria by blood sampling, during the first week of life, but there is not a simple and efficient method to reduce pain during the procedure. Objectives: Prospective randomized trial, to assess if the administration of oral glucose, paracetamol or EMLA, given individually, can reduce the pain caused in newborns by heel prick, in an outpatient setting. Methods: Doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
6
0
5
Order By: Relevance
“…Although this result is consistent with studies in adults, using both EEG (Bromm et al, 1992;Pickering et al, 2013) and fMRI (Pickering et al, 2015), where paracetamol has been shown to reduce brain activity evoked by noxious procedures, previous studies in neonates have provided insufficient evidence to determine the analgesic efficacy of paracetamol for acute procedural pain (Ohlsson and Shah, 2020). While several studies suggest an opioid-sparing effect of paracetamol (Ceelie et al, 2013;Härmä et al, 2016) and reduced need for pain relieveing interventions (Höck et al, 2020), the majority of studies do not demonstrate a reduction in behavioural or physiological responses to commonly performed painful procedures, such as heel lancing (Badiee and Torcan, 2009;Bonetto et al, 2008;Shah et al, 1998) and invasive eye examinations to screen for retinopathy of prematurity (Seifi et al, 2013). The behavioural outcome measures used in these studies may fail to discriminate between pain and distress (Moultrie et al, 2017;Slater, 2019), which could limit conclusions related to analgesic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although this result is consistent with studies in adults, using both EEG (Bromm et al, 1992;Pickering et al, 2013) and fMRI (Pickering et al, 2015), where paracetamol has been shown to reduce brain activity evoked by noxious procedures, previous studies in neonates have provided insufficient evidence to determine the analgesic efficacy of paracetamol for acute procedural pain (Ohlsson and Shah, 2020). While several studies suggest an opioid-sparing effect of paracetamol (Ceelie et al, 2013;Härmä et al, 2016) and reduced need for pain relieveing interventions (Höck et al, 2020), the majority of studies do not demonstrate a reduction in behavioural or physiological responses to commonly performed painful procedures, such as heel lancing (Badiee and Torcan, 2009;Bonetto et al, 2008;Shah et al, 1998) and invasive eye examinations to screen for retinopathy of prematurity (Seifi et al, 2013). The behavioural outcome measures used in these studies may fail to discriminate between pain and distress (Moultrie et al, 2017;Slater, 2019), which could limit conclusions related to analgesic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although this result is consistent with studies in adults, using both EEG (Bromm et al, 1992; Pickering et al, 2013) and fMRI (Pickering et al, 2015), where paracetamol has been shown to reduce brain activity evoked by nociceptive procedures, previous studies in infants have provided insufficient evidence to determine the analgesic efficacy of paracetamol for acute procedural pain (Ohlsson and Shah, 2020). While several studies suggest an opioid-sparing effect of paracetamol (Ceelie et al, 2013; Härmä et al, 2016), the majority of studies do not demonstrate a reduction in behavioural or physiological responses to commonly performed painful procedures, such as heel lancing (Badiee and Torcan, 2009; Bonetto et al, 2008; Shah et al, 1998) and invasive eye examinations to screen for retinopathy of prematurity (Seifi et al, 2013). The behavioural outcome measures used in these studies may fail to discriminate between pain and distress (Moultrie et al, 2017; Slater, 2019), which could limit conclusions related to analgesic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…34 Otro anestésico tópico frecuente es la combinación de lidocaína y prilocaína al 2,5%, pero tampoco ha mostrado buenos resultados al compararlo con terapias no farmacológicas. 35 No se ha visto metahemoglobinemia con el uso de este anestésico 36 ; se han reportado dermatitis de contacto. 37 Recomendación A 3 : la analgesia preventiva con acetaminofén antes del procedimiento no es recomendada ya que es ineficaz.…”
Section: Punción Del Talónunclassified